Testing of the "Gizinesia" Website as an Educational Media for Diabetes Mellitus Patients - Estofany, Fredy; Sitoayu, Laras; Ronitawati, Putri; Nuzrina, Rachmanida; Kuswari, Mury (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Indonesia has diabetes alert status because it ranks 7th out of 10 countries with the highest number of diabetes patients. There are five main pillars in diabetes management: education, medical nutrition therapy, physical activity, pharmacology, and independent blood sugar monitoring. Education is the first pillar that can be done with the help of easily accessible and sustainable media, one of which is the website. One of the important steps in developing educational media is to validate the media by professionals and respondents of the target group. The objective of this study is to know the development and validation of "Gizinesia" as an educational medium for Diabetes Mellitus patients according to professionals and respondents with diabetes. This research is quantitative research with a methodology approach in three steps: development, validity, and evaluation with a sample of 11 professionals and 20 respondents with diabetes. Based on validity tests by professionals, the website content was declared valid with a CVR with a CVI value of ≥ 0.80. The website construct was valid with an average calculation of r≥ 0.632. However, out of 18 items found three invalid items. Based on the validity test by diabetic respondents, the website content was found to be valid with Mean I-CVI = 0.95. However, out of 15 items, 1 item was found to be invalid and the website construct was declared valid with an average r≥ 0.7. However, of the 16 items found two items with low correlation. Therefore, the results of the validation of the "Gizinesia" website as a nutrition education medium for Diabetes Mellitus patients are valid. However, they need improvement by making an illustrated video and following the "10/20/30 Rule".